Integrated Optical Interconnect Architectures for Embedded Systems - O'Connor, Ian.; O'Connor, Ian.; Nicolescu, Gabriela.; Nicolescu, Gabriela. (Embedded Systems,, 2013)
This book provides a broad overview of current research in optical interconnect technologies and architectures. Introductory chapters on high-performance computing and the associated issues in conventional interconnect architectures, and on the fundamental building blocks for integrated optical interconnect, provide the foundations for the bulk of the book which brings together leading experts in the field of optical interconnect architectures for data communication. Particular emphasis is given to the ways in which the photonic components are assembled into architectures to address the needs of data-intensive on-chip communication, and to the performance evaluation of such architectures for specific applications.   Provides state-of-the-art research on the use of optical interconnects in Embedded Systems; Begins with coverage of the basics for high-performance computing and optical interconnect; Includes a variety of on-chip optical communication topologies; Features coverage of system integration and optically-enhanced MPSoC performance;   Offers a single source reference to the latest research, otherwise available only in disparate journals and conference proceedings.